2022
DOI: 10.3389/fphys.2022.830367
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes in the Cardiac RyR2 With Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT)

Abstract: The cardiac ryanodine receptor Ca2+ release channel (RyR2) is inserted into the membrane of intracellular sarcoplasmic reticulum (SR) myocyte Ca2+ stores, where it releases the Ca2+ essential for contraction. Mutations in proteins involved in Ca2+ signaling can lead to catecholaminergic polymorphic ventricular tachycardia (CPVT). The most common cellular phenotype in CPVT is higher than normal cytoplasmic Ca2+ concentrations during diastole due to Ca2+ leak from the SR through mutant RyR2. Arrhythmias are trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…FKBP interacts with the SPRY2 domain and α-solenoid 1 forming part of the corona [ 3 ], approximately 100 nm distant from the ion pore. Many ligands bind in this area and affect channel gating through a cascade of residue re-orientations along signalling pathways through the protein to the pore [ 37 ]. It is suggested that FKBP12 inhibits RyRs by clamping the SPRY2 and α-solenoid 1 domains and that reducing their mobility inhibits the channel [ 32 , 38 ].…”
Section: A Model For the Effects Of Fkbp12 On Ryr2 With Negative Coop...mentioning
confidence: 99%
“…FKBP interacts with the SPRY2 domain and α-solenoid 1 forming part of the corona [ 3 ], approximately 100 nm distant from the ion pore. Many ligands bind in this area and affect channel gating through a cascade of residue re-orientations along signalling pathways through the protein to the pore [ 37 ]. It is suggested that FKBP12 inhibits RyRs by clamping the SPRY2 and α-solenoid 1 domains and that reducing their mobility inhibits the channel [ 32 , 38 ].…”
Section: A Model For the Effects Of Fkbp12 On Ryr2 With Negative Coop...mentioning
confidence: 99%
“…Cell-free experiments have indicated that a vast majority of tested CVPT1 mutations activate the RyR2 channel in response to elevated luminal Ca 2+ [ 181 , 182 , 183 , 184 ]. Although hypersensitivity to cytosolic Ca 2+ and hyposensitivity to cytosolic Mg 2+ could also participate [ 112 , 185 , 186 , 187 , 188 ], more frequent spontaneous Ca 2+ release under conditions of store Ca 2+ overload (SOICR) represents a common defect caused by CPVT1 mutations (comprehensively reviewed in [ 75 , 189 , 190 ]. This inappropriate RyR2 activation results in diastolic SR Ca 2+ leak, which has been suggested to trigger fatal cardiac arrhythmias [ 191 ].…”
Section: The Ryr2 Channel As An Endogenous Target Of Dantrolenementioning
confidence: 99%
“…Not unexpectedly, there is evidence that gain-of-function point mutations in RyR1 and RyR2 increase channel opening through a variety of mechanisms, consistent with the complex organization of these tetrameric multidomain ion channels ( Iyer et al, 2022 ). The variety of possible mechanisms that would allow mutations in different domains to alter channel gating underlines the need for therapies targeted to mutations in particular domains of the protein ( Dulhunty, 2022 ; Dulhunty et al, 2022 ; Iyer et al, 2022 ).…”
Section: More Unanswered Questionsmentioning
confidence: 99%